Reduced left ventricular function and sustained hypertension in women seven years after severe preeclampsia. (31st December 2022) - Gronningsaeter, L.; Skulstad, H.; Quattrone, A.; Langesaeter, E.; Estensen, M. E.
Abstract: Objective . To study left ventricular (LV) function and blood pressure (BP) at a long-term follow-up in women after severe pre-eclampsia. Design . In this single-centre, cross-sectional study, 96 patients were eligible for inclusion. LV function was examined by transthoracic echocardiography including tissue Doppler echocardiography and speckle tracking. BP was measured at rest using repeated non-invasive techniques. Results . We compared 36 patients with early-onset and 33 patients with late-onset pre-eclampsia with 28 healthy controls. Mean age (40 ± 3 years) and median time since delivery (7 ± 2 years) were similar across the study groups. The patients had 18% higher systolic BP (139 ± 15 mmHg) and 24% higher diastolic BP (87 ± 19 mmHg) than controls ( p < .01). Hypertension was present in 23 patients (33%), where the estimated LV mass was 16% higher ( p = .05) than in controls. The LV ejection fraction was 19% lower in the early-onset group (51 ± 4%; p = .01) and 14% lower in the late-onset group (54 ± 6; p = .04) compared with controls. LV global longitudinal strain was 18% lower in the patient group (–17.7 ± 2.1%) compared with controls ( p = .01). Indicative of a more restrictive filling pattern, the diastolic indices showed a lower e′ mean ( p < .01) and subsequently higher E/e′ ratio ( p < .01). There were no significant differences in BP, systolic or diastolic function indices between the patient groups. Conclusion . We found sustained hypertension, higher LV mass and reduced LV systolic and diastolic function 7 y after severe pre-eclampsia. Our findings emphasize the importance of early risk stratification and clinical counselling, and follow-up for such cases.